Disrupting Faculty-on-Faculty Bullying in Academic Medicine: An Innovative Workshop - Maya S. Iyer; David P. Way; Doug MacDowell; Barbara Overholser; Reshma Jagsi; Nancy D. Spector (Association of American Medical Colleges, 2023)
Introduction Bullying, a severe form of mistreatment, occurs when an individual in an authority position intentionally imposes negative persistent behaviors on a target. In academic medicine, bullying is used to impede the target's professional growth. While there is abundant literature on how to disrupt other forms of mistreatment, the literature related to bullying among academic medical faculty members is scarce. Methods We developed an interactive workshop on disrupting faculty-on-faculty bullying in academic medicine, with a focus on gender-based bullying, following Kern's model of curriculum development. The workshop consisted of three didactics on the scope of bullying in academic medicine: identifying bullying behaviors, learning strategies to mitigate bullying, and understanding what constitutes comprehensive antibullying policies. The workshop also included three small-group activities to reinforce learned concepts. Results Eighty-seven faculty attended one of three workshops held over a 6-month period. We received 24 completed evaluations for a 28% rate of return. Most participants rated workshop activities as being well taught and of great value. Many respondents commented that after participating in the workshop, they realized they had likely experienced or witnessed bullying in their careers and that mitigating bullying required effort at multiple levels (individual, institutional, national). Discussion This workshop fills a need in academic medicine through addressing how faculty members and institutions can help themselves and others to disrupt bullying. We will continue to disseminate this workshop at national conferences and at individual institutions. This resource will allow other educators to offer the workshop at their home institutions.